Hyperbilirubinemia and Associated Factors Among Neonates Admitted to the Neonatal Care Unit in Jimma Medical Center. - Asaye, Sintayehu; Bekele, Misgana; Getachew, Aklilu; Fufa, Diriba; Adugna, Tesfaye; Tadese, Edosa (Clinical Medicine Insights: Pediatrics, 2023)
Background: Neonatal hyperbilirubinemia is a widespread and significant clinical problem among neonates worldwide. Globally, every year about 1.1 million babies develop it and the vast majority reside in South Asia and sub-Saharan Africa. Studies on the magnitude and factors associated with neonatal hyperbilirubinemia are limited in Ethiopia. So this study was aimed at assessing the prevalence and associated factors of neonatal hyperbilirubinemia among hospitalized neonates in the neonatal intensive care unit of Jimma Medical Center (JMC), Jimma, South West Ethiopia. Design: Hospital-based cross-sectional study was conducted at JMC from July 24 to October 19, 2020. Methods: A total of 222 neonates with their mothers were included and conveniently selected. Data was collected by interviewing mothers through structured questionnaires and reviewing neonates' medical records using a checklist. Multivariable binary logistic regression analyses were employed to identify factors associated with neonatal hyperbilirubinemia. Results: from a total of neo-maternal pairs included in the studies; the proportion of Neonatal hyperbilirubinemia was found to be 94 (42.3%). Neo-maternal ABO incompatibility 33 (35.1%), prematurity 41 (43.6%), sepsis 35 (37.2%), Neonatal birth asphyxia 20 (21.2%), and Rh isoimmunization 10 (10.6%) was significantly associated with neonatal hyperbilirubinemia. Conclusion: The prevalence of neonatal hyperbilirubinemia in the study setting was high. Antenatal care (including both mother and fetus detail examination and follow-ups) as well as cautions during labor need to focus on since Neonatal hyperbilirubinemia-associated factors were maternal and neonatal. Hence, further assessment, early intervention, and timely treatment are important to mitigate the burdens in neonates due to hyperbilirubinemia.